Noninvasive monitoring of central venous oxygen saturation by jugular transcutaneous near-infrared spectroscopy in pediatric patients undergoing congenital cardiac surgery - Altun, Dilek; Dogan, Abdullah; Arnaz, Ahmet; Yuksek, Adnan; Yalcinbas, Yusuf Kenan; Turkoz, Riza; Sarioglu, Tayyar (TUBITAK SCIENTIFIC \& TECHNICAL RESEARCH COUNCIL TURKEY, 2020)
Background and aim: In patients undergoing congenital cardiac surgery, it is crucial to maintain oxygen demand-consumption balance. Central venous oxygen saturation (ScvO(2)) is a useful indicator of oxygen demand and consumption balance which is an invasive method. Near-infrared spectroscopy (NIRS) is a noninvasive, continuous monitoring technique that measures regional tissue oxygenation. NIRS that is placed over the internal jugular vein cutaneous area (NIRSijv) has the potential to show ScvO(2) indirectly. In this study, we aimed to determine the correlation between ScvO(2) with NIRSijv in pediatric patients undergoing congenital cardiac surgery. Materials and methods: Fifty children participated in the study. Four patients were excluded for the inability of internal jugular vein (IJV) catheterization due to technical difficulties. After anesthesia induction, NI RS probes were placed on the IJV site with ultrasound guidance for the measurement of continuous transcutaneous oxygen saturation. The catheter insertion was also done through the IJV from the other side using ultrasound guidance. Cerebral oxygenation monitoring was done using NI RS with a single pediatric probe placed on the right forehead. Values of NIRSijv, cerebral NI RS (NIRSc) and ScvO(2), were recorded at certain times until postoperative 24th hour. Results: Data were collected at 8 different time points. There was a significant correlation between ScvO(2) and NIRSijv in all measurement time points (r = 0.91), (p = 0.001). The mean bias between ScvO(2) and NIRSijv was 2.92\% and the limits of agreement were from 11\% to -5.2\%. There was a moderate correlation between ScvO(2) and NIRSc (r = 0.45), (13= 0.001). The mean bias between ScvO(2) and NIRSc was 2.7\% and the limits of agreement were from +26\% to -20\%. Conclusion: In this study, we found a strong correlation between ScvO(2) and NI RS measurements taken from the internal jugular vein site. Accordingly, continuous noninvasive monitoring with transcutaneous NIRSijv can be an alternative method as a trend monitor for the central venous oxygen saturation in pediatric cardiac patients undergoing congenital cardiac surgery.
Keywords: Near-infrared spectroscopy; central venous oxygen saturation; mixed venous oxygen saturation; congenital cardiac surgery